AKSESIBILITAS MEDIA SOSIAL DALAM INTERAKSI ANTAR ANGGOTA KELUARGA URBAN - Ditha Prasanti; Putri Limilia (REFORMASI, 2019)
Abstract: This article is the result of further research on the study of the resilience of urban families in the digital era, which focuses on the accessibility of social media in the interaction between members of the urban family. Urban family is an interesting study to be discussed because of the current concept that demands the development of the digital era. Urban families, as family members living in urban areas, have a large level of social media accessibility, so interaction between family members is also possible through social media. This is interesting to discuss because the author wants to reveal the accessibility of social media in the interaction between members of the urban family. In this study, the author uses a qualitative approach, with data collection techniques, in the form of interviews; observation; and documentation study. Accessibility of social media in the interaction between members of the urban family produces varied findings, including the existence of family conflicts caused by the accessibility of social media; enabling the dissemination of information on social media as a result of the interaction of members of the urban family; the emergence of social media group networks as a forum for interaction between members of the urban family. Based on these findings, the authors see the existence of positive and negative points that can be generated as a result of the accessibility of social media used by members of urban families. Keywords: Accessibility, Social Media, Interaction, Urban Family. Abstrak: Artikel ini merupakan hasil penelitian lanjutan tentang kajian ketahanan keluarga urban di era digital, yang memfokuskan pada aksesibilitas media sosial dalam interaksi antar anggota keluarga urban tersebut. Keluarga urban menjadi kajian menarik untuk dibahas karena konsep kekinian yang menuntut perkembangan era digital. Keluarga urban, sebagai anggota keluarga yang tinggal di perkotaan, memiliki tingkat aksesibilitas media sosial yang besar, sehingga interaksi antar anggota keluarga pun sangat memungkinkan dilakukan melaui media sosial tersebut. Hal ini menarik untuk dibahas karena penulis ingin mengungkapkan aksesibilitas media sosial dalam interaksi antar anggota keluarga urban. Dalam kajian ini, penulis menggunakan pendekatan kualitatif, dengan teknik pengumpulan data, berupa wawancara; observasi; dan studi dokumentasi. Aksesibilitas media sosial dalam interaksi antar anggota keluarga urban ini menghasilkan temuan yang bervariatif, di antaranya adalah adanya konflik keluarga yang disebabkan oleh aksesibilitas media sosial tersebut; memungkinkan terjadinya penyebaran informasi hoaks dalam media sosial sebagai hasil dari interaksi anggota keluarga urban; munculnya jaringan group media sosial sebagai wadah interaksi antar anggota keluarga urban tersebut. Berdasarkan temuan tersebut, penulis melihat adanya point positif dan negatif yang dapat ditimbulkan sebagai hasil dari aksesibilitas media sosial yang digunakan oleh anggota keluarga urban. Kata Kunci: Aksesibilitas, Media Sosial, Interaksi, Keluarga Urban.